Changing your body changes your eating attitudes: embodiment of a slim virtual avatar induces avoidance of high-calorie food. Issue 7 (July 2021) - Tambone, Riccardo; Poggio, Giulia; Pyasik, Maria; Burin, Dalila; Dal Monte, Olga; Schintu, Selene; Ciorli, Tommaso; Lucà, Laura; Semino, Maria Vittoria; Doricchi, Fabrizio; Pia, Lorenzo
Abstract: The virtual-reality full-body illusion paradigm has been suggested to not only trigger the illusory ownership of the avatar's body but also the attitudinal and behavioral components stereotypically associated to that kind of virtual body. In the present study, we investigated whether this was true for stereotypes related to body size: body satisfaction and eating control behavior. Healthy participants underwent the full-body illusion paradigm with an avatar having either a larger or a slimmer body than their own, and were assessed for implicit attitudes towards body image and food calorie content at baseline and after each full-body illusion session. Results showed that the illusion emerged regardless of the avatar's body size, whereas the perceived dimension of the own body size changed according to the avatar's body size (i.e., participants felt to be slimmer after embodying their slim avatar and larger after embodying their large avatar). Crucially, we found that implicit attitudes towards food, but not those towards one's own body, were modulated by the size of the virtual body. Compared to baseline, ownership of a slimmer avatar increased the avoidance of high-calorie food, whereas ownership of a larger avatar did not induce changes. Our findings suggest that the illusory feeling of being slimmer drives also the food-related stereotypes associated with that body size, increasing the regulation of eating behaviors. Abstract : Body ownership, Implict bias, food, body image